HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIVITAS DENGAN PRESTASI AKADEMIK SISWA AKUNTANSI DI SMK NEGERI SUKOHARJO - Devi Wulandari; Asri Diah Susanti (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2026)
This study aimed to investigate empirical evidence on the relationship between critical thinking ability and creativity with the academic achievement of Accounting students at SMK Negeri Sukoharjo. This study employs a quantitative approach using a descriptive-correlational method.. The research subjects were all 107 students in class XI of the Accounting and Finance program (AKL) at SMK Negeri Sukoharjo. Data collection was carried out using a critical thinking test (Watson–Glaser Critical Thinking Appraisal), a creativity questionnaire, and documentation of ASAS scores. Prerequisite test results consisting of normality, linearity, multicollinearity, and heteroscedasticity tests showed that the data met the requirements for analysis. Hypotheses were tested using simple correlation, multiple correlation, and the coefficient of determination. The results show that critical thinking skills have a positive but non-significant relationship with academic achievement (r = 0.034; sig. = 0.729), creativity has a positive but nonsignificant relationship with academic achievement (r = 0.074; sig. = 0.452), and critical thinking skills and creativity together have a positive but non-significant relationship with academic achievement (R = 0.076; sig. F Change = 0.739). All three correlation coefficients fall into the very weak category. The coefficient of determination (R Square) of 0.006 indicates that critical thinking skills and creativity jointly contribute only 0.6% to academic achievement, while the remaining 99.4% is influenced by other factors outside this study.Keywords: Academic Achievement; Creativity; Critical Thinking.